DEVELOPMENT OF MULTIMEDIA WEB-BASED PHYSICS LEARNING TOOLS TO STRENGTHEN STUDENTS’ CHARACTERS - Akhlis, Isa; Aryani, Nila Prasetya (Unnes Science Education Journal, 2018)
This research intended to obtain an initial description of students and environment on peace-loving, environmental caring, learning methods, learning materials, and learning media applied in Physics lesson at a high school; moreover, to examine the validity of high school physic learning materials and multimedia web-based physics learning tools in strengthening the students’ characters. The data collection methods employed were (1) documentation, to get the prior data of high school physic materials; (2) observation, to collect the data of students’ initial characters; (3) questionnaire, to obtain the data of learning method, teaching materials, and learning media adopted in the learning process; and (4) validation, to test the developed learning tools’ validity. The results showed that generally, the students have possessed the character of peace-loving, while they rarely owned the environmental caring. In addition, the developed learning tools achieved a good assessment and were declared valid.